Peran Lingkungan Terhadap Perkembangan Sosio-Emosional Anak - Halen Dwistia; Meli Indah Novita Sari; Lailatul Fatimah; Windu Damar Mulyana (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This type of research is qualitative research. This research aims to examine the role of the environment on children's socio-emotional development. The method used in this research is qualitative research with interviews as a data collection technique which was carried out on Saturday 26 October 2024. This research was conducted in the village of Bandar Putih Tua, Anak Ratu Aji, Central Lampung with the research subjects being 5 children aged 7-10 the year that is the data source. The research results show that the family environment has a significant impact on children's emotional management, while the peer environment influences children's social behavior, both positively and negatively. The school environment, on the other hand, plays a role in shaping children's emotional stability and social skills through interactions with teachers and peers. Based on this research, it can be concluded that the environment plays a very important role in children's socio-emotional development, and the role of parents and the regulation of the social environment around children greatly determines their social and emotional development. It is hoped that this research will provide deeper insight into the importance of creating a supportive environment for children's socio-emotional development.